Profil Kondisi Fisik Atlet Bola Voli STKIP PGRI Pacitan - Anung Probo Ismoko; Danang Endarto Putro (Indonesian Journal of Physical Education and Sport Science)
Study purpose. The aim of the study was to determine the physical condition profile of STKIP PGRI Pacitan Bola voli athletes who competed in the East Java POMPROV championship in 2023. The athlete's physical condition used as a benchmark to determine whether the athlete was ready before competing.